Managing business and innovation networks — From strategic nets to business fields and ecosystems - Moller Kristian; Halinen Aino (Elsevier, 2022)
This article introduces the Special Issue of Managing Business and Innovation Networks and makes an independent contribution to the advancement of network management research. The study has three ambitious goals. First, it evaluates the main developments in network management research from 2000 to 2016, focusing on disciplinary openings. Second, it specifies the contributions of recent domain extensions (business fields, ecosystems, platform networks) to network management, and clarifies the role of networks and network management in these domains. Third, it proposes a general theory of network management based on the past 20 years of research in the field and the contributions of SI articles. The theory explains how the factors at three contextual levels – environment, network and actor – influence network management activities, forming patterns of management based on activity configurations. The framework consolidates our fragmented knowledge on network management and paves the way for more advanced research and management. We conclude with suggestions for future research.